2020
DOI: 10.1186/s12934-020-01320-5
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of the Flv3B flavodiiron, enhances the photobiological hydrogen production by the nitrogen-fixing cyanobacterium Nostoc PCC 7120

Abstract: Background: The ability of some photosynthetic microorganisms, particularly cyanobacteria and microalgae, to produce hydrogen (H 2) is a promising alternative for renewable, clean-energy production. However, the most recent, related studies point out that much improvement is needed for sustainable cyanobacterial-based H 2 production to become economically viable. In this study, we investigated the impact of induced O 2-consumption on H 2 photoproduction yields in the heterocyte-forming, N 2-fixing cyanobacteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…6d ). A recent report suggested that overexpressing heterocyst‐specific Flv3B leads to more stable microoxic conditions inside the heterocysts, notably increasing the H 2 production yield, presumably via the bidirectional hydrogenase Hox (Roumezi et al ., 2020 ). In contrast to the unidirectional production of H 2 by nitrogenase, Hox catalyses the reversible reduction of protons to H 2 (Bothe et al ., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…6d ). A recent report suggested that overexpressing heterocyst‐specific Flv3B leads to more stable microoxic conditions inside the heterocysts, notably increasing the H 2 production yield, presumably via the bidirectional hydrogenase Hox (Roumezi et al ., 2020 ). In contrast to the unidirectional production of H 2 by nitrogenase, Hox catalyses the reversible reduction of protons to H 2 (Bothe et al ., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the heterocyst‐specific Flv3B enzyme actively eliminates O 2 thus enabling microoxic interior inside of the heterocyst, which supports diazotrophic growth and nitrogenase enzyme activity under illumination (Ermakova et al, 2014). Accordingly, overexpression of the Flv3B protein resulted in high H 2 photoproduction, even though this phenotype was not linked to enhanced nitrogenase activity (Roumezi et al, 2020). The latter requires further investigations.…”
Section: Engineering Cyanobacteria For Sustainable and Efficient H2 Productionmentioning
confidence: 99%